Longitudinal Follow-Up of Physical Activity During School Recess: Impact of Playground Markings - Baquet, Georges; Aucouturier, Julien; Gamelin, François Xavier; Berthoin, Serge (Frontiers in Public Health, 2018)
To promote physical activity (PA) among children, few studies have reported long-term effects of playground marking during school recess. The aim of this study was to investigate the impact of a playground design on children’s recess PA across 12 months and to evaluate the influence of covariates on the intervention effects with accelerometry data. Two hundred and eighty-three children (aged 6-11 years) were selected from 3 elementary schools. Two experimental schools received a recess-based intervention; the third one served as a control group. The design of playgrounds was based on a multicolored zonal design. Children’s PA was measured with a uniaxial accelerometer twice a day (morning and afternoon recess) during a 4-day school week. Times spent below and above different PA levels, varying from sedentary (SED, <1.5 METs), light PA (LPA, < 4 METs) and from moderate to very high (MVPA, ≥ 4 METs) were calculated before and after 6 and 12-month intervention. A three level (time, pupil, school) multilevel analysis was used to control the intervention effect across time on SED, LPA and MVPA. The playground intervention was effective after 6 months for LPA (+2.5%, CI 0.65/4.29, P<0.01) and after 12 months for MVPA (+3.1%, CI 0.62/5.54, P<0.01). Moreover, negative non-significant intervention effects were found for SED and LPA. Baseline PA and sex were significant covariates to the contrary of body mass index and age. Playground markings intervention can modify positively long-term school recess total PA.